Dermatologists across Europe underestimate depression and anxiety: results from 3635 dermatological consultations3. (16th May 2018) - Dalgard, F.J.; Svensson, Å.; Gieler, U.; Tomas‐Aragones, L.; Lien, L.; Poot, F.; Jemec, G.B.E.; Misery, L.; Szabo, C.; Linder, D.; Sampogna, F.; Evers, A.W.M.; et al.
Summary: Background: It was recently demonstrated that a significant number of patients with common skin diseases across Europe are clinically depressed and anxious. Studies have shown that physicians not trained as psychiatrists underdiagnose depression. This has not been explored among dermatologists. Objectives: To estimate the concordance between clinical assessment of depression and anxiety by a dermatologist and assessment with the Hospital Anxiety and Depression Scale (HADS). Methods: The study was an observational cross‐sectional multicentre study of prevalent cases of skin diseases in 13 countries in Europe. Consecutive patients were recruited in outpatient clinics and filled in questionnaires prior to clinical examination by a dermatologist who reported any diagnosis of skin disease and signs of mood disorders. Results: Analysis of the 3635 consultations showed that the agreement between dermatologist and HADS was poor to fair (lower than 0·4) for all diagnosis categories. The true‐positive rate (represented by the percentage of dermatologists recognizing signs of depression or anxiety in patients with depression or anxiety as defined by a HADS value ≥ 11) was 44·0% for depression and 35·6% for anxiety. The true negative rate (represented by the percentage of dermatologists not detecting signs of depression or anxiety in non‐depressed or non‐anxious patients defined by HADS‐value < 11) was 88.8% for depression and 85.7% for anxiety. Conclusions: Dermatologists in Europe tend to underestimate mood disorders. The results suggest that further training for dermatologists to improve their skills in diagnosing depression and anxiety might be appropriate. When present, the psychological suffering of patients with dermatological conditions needs to be addressed. Abstract : What's already known about this topic? It has recently been demonstrated that patients with common skin diseases have more depression and anxiety than controls. Research has shown that physicians who are not trained as psychiatrists miss depression in their patients. What does this study add? A large proportion of cases of depression in patients with skin disease are not diagnosed by dermatologists. These results indicate that further training for dermatologists to assess depression and anxiety might be appropriate. Linked Editorial:  Montgomery and Thompson. Br J Dermatol 2018;179 :237–238 . Plain language summary available online Respond to this article